Respostas
respondido por:
2
a) f(0)
f(0) = 1 - 5*(0)
f(0) = 1 - 0
f(0) = 1
b) f(x) = -2
1 - 5x = -2
5x = 1 + 2
5x = 3
x = 3/5
f(0) = 1 - 5*(0)
f(0) = 1 - 0
f(0) = 1
b) f(x) = -2
1 - 5x = -2
5x = 1 + 2
5x = 3
x = 3/5
respondido por:
1
a) f(0)
f(x) = 1 - 5x
f(0) = 1 - 5 · 0
f(0) = 1 - 0
f(0)= 1
b) f(x)= - 2
f(x) = 1 - 5x
-2 = 1 - 5x
-2 -1 = -5x
-3 = - 5x
-3 · (-1) = -5x · (-1)
3 = 5x
5x = 3
x = 3/5
Bons estudos!
f(x) = 1 - 5x
f(0) = 1 - 5 · 0
f(0) = 1 - 0
f(0)= 1
b) f(x)= - 2
f(x) = 1 - 5x
-2 = 1 - 5x
-2 -1 = -5x
-3 = - 5x
-3 · (-1) = -5x · (-1)
3 = 5x
5x = 3
x = 3/5
Bons estudos!
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás